Prabhukumar, K.M., R. Jagadeesan, G. Prasad, B.N. Nagaraj, V.N. Naveen Kumar, V. Bhaskar& Indira Balachandran (2017) Two new taxa of Impatiens (Balsaminaceae) from southern parts of Western Ghats, India. Phytotaxa 296 (3): 281–286. - Prabhukumar, Konickal Mambetta; Jagadeesan, Raveendran; Prasad, Gopalakrishnan; Nagaraj, Bhagavathi Amma Natarajan Achari; Kumar, Vannaratta Veettil Naveen; Veeralinga, Bhaskar; Balachandran, Indira (Phytotaxa, 2017)
N/A